ANNUAL FINANCIAL STATEMENTS IN CAMEROON: REASONS AND EXPLANATIONS OF THE CHOICE OF ASSET VALUATION METHODS - MAYEGLE , François-Xavier; TEMWA , ROGER (Revue du contrôle, de la comptabilité et de l’audit, 2022)
This article aims to understand the reasons and explanations for the choice of asset valuation methods when preparing annual financial statements within Cameroonian entities. To achieve this objective, initially an observation of the annual financial statements of 80 entities was made over a period of 10 years, which enabled us to observe a preference for the historical cost method compared to other methods. Secondly, seven entities agreed to provide us with the reasons and explanations for their choice via semi-structured interviews. It emerges that the cost factor of the present value method is that factor which directs the entities towards the historical cost having a zero cost. This cost is explained by the existence of the fees to be paid to the appraisers, the tax on the difference in the revaluation and the insurance premium which is a function of the value of the balance sheet. Other reasons, such as the subjectivity of current value methods and the flexibility of the historical cost method, were rarely mentioned by respondents. The cost factor of the present value method seems to outweigh the others.